PERAN MANAJEMEN PEMASARAN GLOBAL DALAM MENINGKATKAN KEPUASAN KONSUMEN - Suhairi Suhairi; Dian Irmawani; Mira Nur Aisah; Sonia Purba; Amalia Munajah Nasution (CV. Aksara Global Akademia, 2023)
The contemporary era of globalization has connected everything. Thus, it is impossible to understand many economic, political and cultural relations from a single perspective. Almost all over the world, globalization has changed the way people live, work and consume. Thus the phenomenon of modernization was born, modernization is a process in which society becomes increasingly dependent on technology. In the world of business, technology is one of the most important things in marketing to the public, especially global marketing. So this research aims to see how the role of global marketing management in increasing consumer satisfaction, especially in Indonesia.